A low-gluten diet induces changes in the intestinal microbiome of healthy Danish adults - Hansen, Lea B. S.; Roager, Henrik M.; Søndertoft, Nadja B.; Gøbel, Rikke J.; Kristensen, Mette; Vallès-Colomer, Mireia; Vieira-Silva, Sara; Ibrügger, Sabine; Lind, Mads V.; Mærkedahl, Rasmus B.; Bahl, Martin I.; Madsen, Mia L.; et al. (Nature communications, 2018)
Adherence to a low-gluten diet has become increasingly common in parts of the general population. However, the effects of reducing gluten-rich food items including wheat, barley and rye cereals in healthy adults are unclear. Here, we undertook a randomised, controlled, cross-over trial involving 60 middle-aged Danish adults without known disorders with two 8-week interventions comparing a low-gluten diet (2 g gluten per day) and a high-gluten diet (18 g gluten per day), separated by a washout period of at least six weeks with habitual diet (12 g gluten per day). We find that, in comparison with a high-gluten diet, a low-gluten diet induces moderate changes in the intestinal microbiome, reduces fasting and postprandial hydrogen exhalation, and leads to improvements in self-reported bloating. These observations suggest that most of the effects of a low-gluten diet in non-coeliac adults may be driven by qualitative changes in dietary fibres. Gluten-free diets are increasingly common in the general population. Here, the authors report the results of a randomised cross-over trial involving middle-aged, healthy Danish adults, showing evidence that a low-gluten diet leads to gut microbiome changes, possibly due to variations in dietary fibres.